Insights into the mechanism of the cyanobactin heterocyclase enzyme - Ge, Y; Czekster, C; Miller, O; Botting, C; Schwarz-Linek, U; Naismith, J (American Chemical Society, 2019)
Cyanobactin heterocyclases share the same catalytic domain (YcaO) as heterocyclases/cyclodehydratases from other ribosomal peptide (RiPPs) biosynthetic pathways. These enzymes process multiple residues (Cys/Thr/Ser) within the same substrate. The processing of cysteine residues proceeds with a known order. We show the order of reaction for threonines is different and depends in part on a leader peptide within the substrate. In contrast to other YcaO domains, which have been reported to exclusively break down ATP into ADP and inorganic phosphate, cyanobactin heterocyclases have been observed to produce AMP and inorganic pyrophosphate during catalysis. We dissect the nucleotide profiles associated with heterocyclization and propose a unifying mechanism, where the γ-phosphate of ATP is transferred in a kinase mechanism to the substrate to yield a phosphorylated intermediate common to all YcaO domains. In cyanobactin heterocyclases, this phosphorylated intermediate, in a proportion of turnovers, reacts with ADP to yield AMP and pyrophosphate.